Pemanfaatan Limbah Kotoran Sapi Menjadi Pupuk Organik Sebagai Upaya Mendukung Usaha Peternakan Sapi Potong di Kelompok Tani Ternak Mandiri Jaya Desa Moropelang Kecamatan Babat Kabupaten Lamongan - Solikhul Huda; Wiwi Wikanta (Universitas Muhammadiyah Surabaya, 2017)
Cattle farming in Indonesia is still concerned with livestock productivity and has not maximized the utilization of cow dung waste (teletong) of economic value. The waste of cow dung (teletong) produced should no longer be a burden of business costs but a result of having high economic value and if possible equivalent to the economic value of the main product (meat). The purpose of this research is to study the utilization of cow dung into organic fertilizer that support the business of fattening beef cattle. The method used in this research is descriptive method with data collection method of observation and interviews of livestock farmer group and supported by literature study. Based on the results of observations and interviews obtained the results that members of Livestock Farmers Group Jaya already utilize and manage the waste of cow dung into organic fertilizer with economic value to sell to members for agricultural land fertilizer rice, watermelon and cantaloupe. The reason for the use of cow dung as fertilizer is usually because the goods are easy to obtain, relatively cheap and give better results.